If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8/3=x11/3
We move all terms to the left:
8/3-(x11/3)=0
We add all the numbers together, and all the variables
-(+x11/3)+8/3=0
We get rid of parentheses
-x11/3+8/3=0
We multiply all the terms by the denominator
-x11+8=0
We add all the numbers together, and all the variables
-1x^11+8=0
We do not support expression: x^11
| 2x*x-9x+7=0 | | 2(t-2)+2=2(2t+-5) | | –5x–6=19 | | 3-5a÷6=-10 | | 90+39+69+2x=180 | | 2x+7=x11 | | 42+92+68+2x=180 | | 60=7r-3 | | 2(x-3)=4-(5x-11) | | 5x-2(x-2)=19 | | 75+5x-10+6x-6=180 | | j−20=-1 | | 3(x-3)+1=15 | | f−9=-4 | | X-1=4-(x+5) | | 11/3x=42.50 | | (X-10)/2+2/5=-x/3 | | 2p-4/3p-2=-2/3 | | -6(2x-9)=-12-54 | | 74-1x=984x | | 6x+9x=4x+25 | | 12y+-6=10 | | F(4)=12x+7 | | A=6x-35° | | 204-v=104 | | 10=(x-(0.15x+125))/x | | 62-v=280 | | 293=-x+156 | | 9w=6w+9 | | 10x=x-(0.15x+125) | | 9w=6w | | -7x=+2=-4x-7 |